2005
DOI: 10.1523/jneurosci.0419-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Cortical Pathways for Processing Tool versus Animal Sounds

Abstract: Human listeners can effortlessly categorize a wide range of environmental sounds. Whereas categorizing visual object classes (e.g., faces, tools, houses, etc.) preferentially activates different regions of visually sensitive cortex, it is not known whether the auditory system exhibits a similar organization for different types or categories of complex sounds outside of human speech. Using functional magnetic resonance imaging, we show that hearing and correctly or incorrectly categorizing animal vocalizations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
259
2
2

Year Published

2008
2008
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(305 citation statements)
references
References 70 publications
(98 reference statements)
34
259
2
2
Order By: Relevance
“…Hearing and categorizing animal vocalizations preferentially activated the middle portion of the superior temporal gyri bilaterally (a region that is not related to motor act coding), whereas hearing and categorizing sounds of tools that were manipulated by hands activated the parieto-frontal mirror circuit 53 . Similarly, it was shown that listening to the sound of hand and mouth motor acts activated the parieto-frontal mirror network 54 .…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 99%
“…Hearing and categorizing animal vocalizations preferentially activated the middle portion of the superior temporal gyri bilaterally (a region that is not related to motor act coding), whereas hearing and categorizing sounds of tools that were manipulated by hands activated the parieto-frontal mirror circuit 53 . Similarly, it was shown that listening to the sound of hand and mouth motor acts activated the parieto-frontal mirror network 54 .…”
Section: Box 1 | Mirror Neurons In Other Parietal Areasmentioning
confidence: 99%
“…Apart from the well documented activations within auditory regions, environmental sounds related to actions were shown to co-activate parts of prefrontal, premotor and motor cortices bilaterally (Lahav et al 2007;De Lucia et al 2009) or predominantly on the left side (Lewis et al 2005;Pizzamiglio et al 2005;Gazzola et al 2006;Hauk et al 2006;Doehrmann et al 2008). The specific involvement of the primary motor cortex was demonstrated by transcranial magnetic stimulation (TMS); motor evoked potentials (MEPs) to stimulation of the hand area were shown to be larger while subjects listened to manualaction-related than unrelated sounds (Aziz-Zadeh et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…Relevant significant interactions were specified by calculating reduced ANOVAs 2 Animal sounds are typically characterized by a high HNR in contrast to other types of environmental sounds, as e.g., household sounds (cf. Lewis et al, 2005). As a consequence of the applied stimulus manipulation, the HNR was lower for the unfamiliar than the familiar stimulus [1.22 vs. 6.05 dB (determined using default parameters with Praat, freely available phonetics software, http://www.fon.hum.uva.nl/praat/)].…”
Section: Statistical Data Analysismentioning
confidence: 99%
“…To date, the processing of environmental sounds has mainly been studied when sounds were processed attentively (e.g., van Petten and Rheinfelder, 1995;Lewis et al, 2005;Cummings et al, 2006;Lenz et al, 2007;Murray et al, 2008). However, as familiar environmental sounds might convey behaviorally and biologically relevant information, processing advantages for familiar sounds might be expected even when sounds are processed outside the focus of attention.…”
Section: Introductionmentioning
confidence: 99%